Perbedaan Praktik Manajemen Laba pada Perusahaan Berbasis Syariah dan Non Syariah - Nur Muhammad Abdilah Hamijaya; Rintan Nuzul Ainy (Universitas Jember, 2022)
Investment interest from the public from year to year continues to increase, not only those who have a lot of capital but people who have limited capital make investments. Various conveniences of investors in investing can be seen from the various existing application platforms. Investors in seeing the company's performance, one of which uses financial statements. However, there is a behavior of the company's management not displaying actual performance such as earnings management, it is based on individual interests and harms other parties who have a tendency not to comply with sharia principles. This study uses a quantitative approach with secondary data in the form of financial statements of Consumer Non-Cyclicals sector companies registered with ISSI and those not registered with ISSI in 2018-2020. The measurement of variables uses a modified jones model analysis in measuring the amount of profit management carried out by the company. The results of this study showed that there was no difference in earnings management practices in Consumer Non-Cyclicals sector companies registered with ISSI and those not registered with ISSI. Although there are differences on average, the differences do not occur significantly in statistics. Keywords: Earnings Management, Modified Jones Model, Consumer Non Cyclicals